2006
DOI: 10.1080/01446190500184444
|View full text |Cite
|
Sign up to set email alerts
|

Benefit evaluation for off‐site production in construction

Abstract: Evaluating to what extent a component or building system should be produced offsite is inadequate within the industry. The potential benefits of off-site production (OSP) are commonly cited when justifying an OSP approach, yet holistic and methodical assessments of the applicability and overall benefit of these solutions, to a particular project, have been found to be deficient. Common methods of evaluation simply take material, labour and transportation costs into account when comparing various options, often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
179
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(201 citation statements)
references
References 2 publications
0
179
0
Order By: Relevance
“…Some argue that the cost premium of specifying factory-fitted bathroom pods can even rise up to 30% compared with traditional bathroom fit-outs (see Waterman, 2006). To counter this view, research at Loughborough University (Blismas et al, 2006) has established that the main reason that the first costs of offsite solutions are often considered to be more expensive is that the comparison is not sensitive enough to the real outturn costs encountered on real projects. The decision support tool IMMPREST (www.IMMPREST.com) has been developed to provide a means for fair and accurate comparison of real value between offsite and on-site options (Blismas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some argue that the cost premium of specifying factory-fitted bathroom pods can even rise up to 30% compared with traditional bathroom fit-outs (see Waterman, 2006). To counter this view, research at Loughborough University (Blismas et al, 2006) has established that the main reason that the first costs of offsite solutions are often considered to be more expensive is that the comparison is not sensitive enough to the real outturn costs encountered on real projects. The decision support tool IMMPREST (www.IMMPREST.com) has been developed to provide a means for fair and accurate comparison of real value between offsite and on-site options (Blismas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pasquire and Gibb (2002) reported that decisions to use offsite were largely based on anecdotal evidence rather than rigorous data as no formal measurement procedures or strategies were available. Blismas et al (2006) presented further evidence demonstrating that decisions to compare traditional and offsite technological solutions for construction in general were largely based on material, labor and transportation costs, whilst other cost-related items such as site facilities, crane use and rectification of works were disregarded or buried within the nebulous preliminary cost items, and softer issues such as health & safety, effects on management and process benefits were either implicit or disregarded. The industry, as a whole, still sees a fragmented cost-driven, rather than systematic value-based, decision culture prevailing in construction technology evaluation and selection practice.…”
Section: Building System Selection: Decision Criteriamentioning
confidence: 98%
“…This significance was highlighted in a recent survey of large UK housebuilders (Pan et al 2008) which reveals that the housebuilders assessed the potential for offsite-MMC applications against a wide range of factors including technical requirements, cost, time, site integration and logistical concerns, customer choice options, sales impacts, mortgage issues, and site constraints. Blismas et al (2006) suggested that a wider account of value-based measures including quality, health, safety, sustainability, and logistics as the means of broadening the comparative exercise from the one-dimensional cost basis to a multi-dimensional valuebased system. However, decision criteria derived on a value-laden basis have relative and context-specific features.…”
Section: Reflecting Organizational Contexts?mentioning
confidence: 99%
See 1 more Smart Citation
“…Having said that, plenty of the research conducted indicates that a controlled environment, such as the one presented in modular construction methods, where components are manufactured off-site in a continuous flow process, allows a lot of benefits to be achieved. These advantages can be realised in terms of productivity, safety and environmental performance [4], [12].…”
Section: Introductionmentioning
confidence: 99%